Driving cost efficiency through operational excellence and sustainability of SMEs in Barru Regency, South Sulawesi, Indonesia - Suriani, Seri; Baharuddin, Sitti Mujahida; Nur, Indrayani; Abubakar, Herminawaty; Abustan, (International Journal of Management and Sustainability, 2024)
This research aims to analyze the factors that influence the cost efficiency and operational excellence of SMEs in Barru Regency, South Sulawesi. This research also aims to examine the direct and indirect influence of the cost efficiency and operational excellence on increasing SME productivity. Formulate a model for cost efficiency, acceleration, and sustainability of SMEs in Barru Regency. This research uses a qualitative-quantitative concurrent triangulation approach. Data was collected through observation, in-depth interviews, surveys, and documentation involving 219 respondents, and quantitative data was analyzed using SMART PLS. The research results show that the factors that influence cost efficiency and operational excellence in SMEs are technology, quality improvement, operational resilience and continuity, and operational targets. Reviewing raw material costs and direct labor costs for SMEs can achieve cost efficiency. Cost efficiency will increase the competitive advantage of SMEs. Apart from that, there is a direct influence of 63.8% and an indirect influence of 84.8% on cost efficiency and operational excellence on the sustainability of SMEs, indirectly increasing productivity in aspects of product quality, production continuity, and operational targets will accelerate SMEs in Barru Regency. The study concluded that cost efficiency drives SMEs acceleration by fostering operational excellence, which in turn promotes SME sustainability.